Species Identification of Food Spoilage and Pathogenic Bacteria by MALDI-TOF Mass Fingerprinting - Böhme, Karola; Fernández-No, Inmaculada C.; Barros-Velázquez, Jorge; Gallardo, Jose M.; Cañas, Benito; Calo-Mata, Pilar (IntechOpen, 2012)
None